NEW LATE SILURIAN AND DEVONIAN ORTHOCERATOIDS FROM NOVAYA ZEMLYA - Zhuravleva F.A. (My University, 2003)
New genera based on new type species, Paramichelinoceras (P. agatovense), Oisengoceras (O. burskyi), Mimokionoceras (M. valentinae), Neritoceras (N. rakovense), Dawsonoceroides (D. nekhvatovensis), Eomooreoceras (E. kabaniense), and Neokionoceras (N. podgornense) and new species, Neokiononoceras? aequale, Paramooreoceras zhonglovichense, and Agnostoceras kuklini, are described. The species Orthoceratites anguliferus Archiac et Verneuil, 1841 is reexamined.
Keywords: Devonian; Silurian; Paleozoic::Devonian; Paleozoic::Silurian; Палеозой::Девонская; Палеозой::Силурийская